HUBUNGAN PENGETAHUAN PUS YANG TIDAK KB DI DESA C KABUPATEN PURWAKARTA - Rukiah, Ai Yeyeh (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2021)
Background: According to the data of Family Planning Civil Registry Welfare Agency (BKCS-KB) of C Village in April 2019, number of reproductive age couples in C Village region were 451 people, and 148 of them did not use Family Planning. Method: This study is descriptive with cross sectional approach using chi square and Kolmogorov Smirnov test. Populations of this study were all 148 reproductive age couples (PUS) who did not use contraception or Family Planning. The populations were taken using random sampling technique get 108 of people. Results: Based on the results of the study, variables related to knowledge reproductive age couples (PUS) who did not use contraception or Family Planning in C Village with a p-value <0.05 were religious factors with a p-value of 0.003 (p-value <0.05) and employment factors with a p-value of 0.05. value 0.043 (p-value <0.05), while the age factor with a p-value of 0.104 (p-value> 0.05), education factor with a p-value of 0.403 (p-value> 0.05) which means age and education variables have not corellation with knowledge reproductive age couples (PUS) who did not use contraception or Family Planning in C Village. Conclusion: Based on the study, it can be concluded that the hypothesis is failed to be refused, which means that there is correlation between factors of age, religion, job, education, and culture with the reason of why reproductive age couples do not use Family Planning.